Explanation of Ecosystem Accounting Criteria in Iraqi Industries - AlqarahGhouli, Ayad Abed Hameed; Maleki, Alireza Hassan; Saheb Shaker, Ameer; Rahimi Dastjerdi, Mohsen (Business, Marketing, and Finance Open, 2024)
The purpose of environmental accounting is to develop information that assists managers in evaluating performance, control, decision-making, accountability, and reporting for an organization or company. The aim of this study is to explain the criteria of ecosystem accounting in Iraqi industries. The collection and analysis of data in this research were conducted through interviews with professional accounting experts in Iraq in 2025. The statistical population consisted of managers of leading companies and university faculty members with activities related to the research topic. Since the present study emphasizes the formation of a conceptual framework or the development of theory and requires the elicitation of experts’ tacit knowledge in this domain, the “thematic analysis” strategy was employed. Furthermore, a type of purposive sampling was used for data collection, and the interviewed experts served as the primary research sources. Accordingly, to identify the ecosystem accounting criteria in Iraqi industries under current conditions, the required qualitative data were collected through in-depth and exploratory individual interviews with purposefully selected academic experts. Using content analysis as a research technique, the main and subsidiary themes and factors were identified and analyzed. These themes served as the basis for developing and explaining the criteria of ecosystem accounting in Iraqi industries. The overall findings highlight a positive trajectory in Iraqi industries, in which environmental accounting—including environmental cost accounting, carbon accounting, and sustainability reporting—explicitly contributes to the improvement of ecosystem accounting criteria.